Roman divination - a discourse on the treatise of cicero, the statesman (2006)
This article addresses a philosophical trend in the ancient Greco- Roman world: making efforts to rid men's minds of fears that were outgrowth of ignorance concerning natural laws that govern the material universe and the perception of the supernatural realm. While such attempt may not necessarily be seen as discrediting the divine agency, the philosopher, Cicero, recognises the need to root out the thought of arbitrary celestial involvement in human affairs: groundless terrors, unfounded and hasty judgments that subject people to questionable practices. The essay is a discussion of a statesman's critical appraisal of an invaluable aspect of Roman religion divination, vis-a-vis man's need to rationally bear more responsibility for his actions. The work highlights the arguments of Cicero in his treatise. Divinatione, that identify the practice of divination among the Romans with superstition and provide an index to the subject of superstition, even in a modem African society with a similar propensity.